2022
DOI: 10.1021/acs.inorgchem.2c02085
|View full text |Cite
|
Sign up to set email alerts
|

White Light-Emitting Diodes Based on One-Dimensional Organic–Inorganic Hybrid Metal Chloride with Dual Emission

Abstract: White-light emissive organic−inorganic hybrid metal halides (MHs) have shown promising potential applications in solid-state lighting. As one-dimensional (1D) MHs for white-light emission remain rare and the key role of halogen regulation in 1D hybrid MHs for broadband emission (BE) has not been well established yet, herein, we report a family of 1D hybrid MHs TMGPbX 3 (TMG = 1,1,3,3-tetramethylguanidine, X = Cl − , Br − , or I − ) to systematically explore the influence of halogen on crystal structures and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…This enhanced thermal stability could be attributed to the increased rotational barrier introduced by the heavier Br atoms. The distorted asymmetric octahedral conformation of PCl further reduces the rotational energy barrier, making it significantly less thermally stable compared to PBr . , The good air stability of these two hybrid perovskites may result from the assembly of the organic and inorganic moieties into a three-dimensional supramolecular framework via hydrogen bonding and Coulombic interactions . Additionally, compared to highly volatile small-molecular organoammonium cations, the selected dipyridine organic molecule, with its rigid conjugated structure upon protonation, enhances the stability of PCl and PBr …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This enhanced thermal stability could be attributed to the increased rotational barrier introduced by the heavier Br atoms. The distorted asymmetric octahedral conformation of PCl further reduces the rotational energy barrier, making it significantly less thermally stable compared to PBr . , The good air stability of these two hybrid perovskites may result from the assembly of the organic and inorganic moieties into a three-dimensional supramolecular framework via hydrogen bonding and Coulombic interactions . Additionally, compared to highly volatile small-molecular organoammonium cations, the selected dipyridine organic molecule, with its rigid conjugated structure upon protonation, enhances the stability of PCl and PBr …”
Section: Resultsmentioning
confidence: 99%
“…30 These excitons tend to be trapped in the lattice potential well, leading to the emission of self-trapped excitons (STEs), which is characterized by a large Stokes shift and a broad emission spectrum. 10,31 On the basis of the observed luminescence characteristics, we attribute the LE emission peak at 550 nm of PCl to the emission of STEs 13,21,29 and the HE band at 430 nm to the emission of the free excitons (FEs) of the organic cations. 25 The greenishyellow broad emission of PBr is believed to arise from the STEs of the perovskites.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, free excitons (FEs) captured by organic cations always exhibit high-energy emission. Several related reports have shown that a number of low-dimensional hybrid halides are exhibiting double emission bands, which are generated by the STEs-induced broadband emission and the FEs-assisted narrow emission. With the synergistic effect of STEs and FEs, the adsorption of the OIMHs can realize dual-band emission, thus greatly broadening the emission range.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of STEs and free excitons (FEs) can easily lead to dual emission bands, which are favorable conditions for the formation of white light emission. [35][36][37] Recently, a large number of white-emitting lead-based hybrid perovskites, such as 2D perovskite (2meptH 2 )PbCl x Br 4−x (2mept = 2-methyl-1,5-diaminopentane, x = 0-4), 38 1D hybrid perovskite TMGPbX 3 (TMG = 1,1,3,3-tetramethylguanidine, X = Cl − , Br − or I − ) 39 and 0D (TAE) 2 [Pb 2 Cl 10 ](Cl) 2 (TAE = tris(2aminoethyl)ammonium(C 6 N 4 H 22 )) 40 single crystals, have been reported. These hybrid lead-based halides all exhibit excellent optical properties and double emission bands resulting from the broadband yellow-green emission induced by STEs and the narrow blue emission spectrum assisted by FE.…”
Section: Introductionmentioning
confidence: 99%